Comparison of Effects of Botulinum Toxin Injection Between Subacute and Chronic Stroke Patients: A Pilot Study. Issue 7 (February 2016) - Lim, Young-Ho; Choi, Eun-Hi; Lim, Jong Youb
Abstract : Abstract: The aim of this study was to compare the effects of botulinum toxin injection between subacute and chronic stroke patients. Eighteen stroke patients (9 subacute and 9 chronic) with spasticity of 1+ or higher in the hemiplegic elbow or wrist joint, based on the modified Ashworth scale were recruited. Modified Ashworth scale, modified Tardieu scale, manual muscle testing, passive range of motion, Brunnstrom stage, modified Barthel index, and Fugl-Meyer scale evaluations of the hemiplegic upper extremity were performed just before the injection and 4 weeks later. A total dose of 200 U of botulinum toxin type A was injected into each patient. One or more of the elbow flexor muscles and one or more of the wrist flexor or finger flexor muscles were included. Modified Ashworth scale, manual muscle testing, passive range of motion, and modified Barthel index results were improved in subacute patients only. However, modified Tardieu scale for the elbow and Fugl-Meyer scale results were improved in both groups, and the improvement was comparable. In conclusion, botulinum toxin injection in subacute patients was more helpful for spasticity, contracture, and function than in chronic patients. However, beneficial effects of botulinum toxin injection on spasticity and function in chronic patients were found in the assessments of the modified Tardieu scale and Fugl-Meyer scale.